العلاقات الصينية العربية في القرنين الثامن عشر والتاسع عشر: نموذج ثقافة الاعتراف الشرقي بين الحضارات (Chinese-Arab Relations in the 18th & 19th Centuries: An Example of the Civilizational Recognition in the East) - al-Ghamidi, Hassna (Journal of Al-Tamaddun, 2017)
Sino-Arab relations are one of the most significant bright cultural relations in the history of peoples and civilizations. From its first inception in prehistoric times and passing through the different stages in the Chinese history of the Imperial families’ rule, and the ages of the Islamic Caliphate in the Muslim world to the emergence of contemporary political relations in 1939; the Sino-Arab relations remained a bright model of understanding one another and embracing the culture of dialogue and coexistence amongst peoples and religions. The significance of this topic is manifest in this time with the emergence of China as an international superpower that now controls a large part of the global economy, and it’s also highlighted in the need of Arabs to redraw their century-old political alliances resulted from the impacts of the cold war between the East and West camps, particularly with the rapid decline of Western and US control and dominance on the global economy and politics with the beginning of the twenty-first century. This research examined the historical roots of the Arab-Chinese relations since its inception in the prehistorically age, all the way to the 18th and 19th centuries. In addition, the research focused on the cognitive aspects of the historical relationship between the two parties. The knowledge and scientific production of both parties is displayed in order to show the historical origins of the exchanged positive cognitive images between them. Then the article turned to address the major historical stages of the Arab-Chinese relations from the period before Islam, passing through the eras of Islamic caliphate and up to the modern Ottoman rule of the Arab lands, until the era of establishing Arab nation-states in the world after the First World War. The research is concluded by a historical analysis of the emergence of the exchanged positive trend in cognitive images of the Arabs and the Chinese for each other.